2008
DOI: 10.1111/j.1365-2028.2008.00929.x
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Genus Ficus L. (Moraceae) in farmlands and pastoral areas in Buganda region, central Uganda

Abstract: Ficus species are found in all tropical habitats occurring as epiphytes or terrestrials, and dominate agricultural ecosystems as shade trees or live fencing. Ecologically, they are indicators of ground water and keystone species providing fruit for frugivores. Their pollination is highly specialized, the pollinating wasps having co‐evolved with the host Ficus species. The study was conducted in Buganda where some species are integrated in the coffee/banana agriculture as shade trees, and a source of bark cloth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 3 publications
0
3
0
1
Order By: Relevance
“…Species such as M. lutea can be harvested for poles, M. excelsa for timber, C. africana for boat construction wood and F. natalensis for bark cloth. In the central region of Uganda, the bark of F. natalensis is used to make a cultural cloth called 'olubugo' that is used in a range of rituals such as funerals, succession and naming (Ipulet & Kasenene 2008). F. natalensis profusely regenerates through seed and vegetatively and is therefore widely planted and retained on farm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Species such as M. lutea can be harvested for poles, M. excelsa for timber, C. africana for boat construction wood and F. natalensis for bark cloth. In the central region of Uganda, the bark of F. natalensis is used to make a cultural cloth called 'olubugo' that is used in a range of rituals such as funerals, succession and naming (Ipulet & Kasenene 2008). F. natalensis profusely regenerates through seed and vegetatively and is therefore widely planted and retained on farm.…”
Section: Discussionmentioning
confidence: 99%
“…In coffee farming systems, farmers maintain some indigenous and grow exotic tree species to minimize competition with coffee plants while helping to ameliorate climate changes, maintain soil fertility and provide important goods such as timber, fuel wood and fruit (Beer et al 1997;Albertin & Nair 2004;Bandeira et al 2005;Soto-Pinto et al 2007). These ecosystem goods and services help to lower the cost of production as well as diversify farm production and benefits (Beer et al 1997;Peeters et al 2003;Albertin & Nair 2004;Soto-Pinto et al 2007;Méndez et al 2007;Ipulet & Kasenene 2008;Isabirye et al 2008;Rice 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Jumlah jenis Ficus yang ditemukan di Gunung Tilu ini sama dengan jumlah jenis Ficus hasil penelitian Kumar et al, (2011) di Suaka Margasatwa Katerniaghat, Uttar Pradesh India namun lebih kecil dengan keberadaan jenis Ficus spp. di hutan konservasi Prof Soemitro Djojohadikusumo sebanyak 20 jenis (Nur'aini et al, 2013), hutan di Mexico 21 jenis (Serrato et al, 2005), hutan hujan dataran rendah Kalimantan sebanyak 27 spesies (Harrison et al, 2003) dan lahan pertanian (32 jenis) di wilayah Buganda Uganda Tengah (Ipulet, 2008 Terestrial. Rambut internal tidak ada.…”
Section: Hasil Dan Pembahasan Populasi Marga Ficusunclassified
“…The total number of Ficus species found in this area is smaller than at Prof. Soemitro Djojohadikusumo conservation forest in PT. Tidar Kerinci Agung (TKA), Sumatera Barat with 20 species (Nur'aini et al 2013), 27 species found at a lowland rainforest in Kalimantan (Harrison et al 2003) and 32 species found at agricultural land in the Buganda region of Central Uganda (Ipulet 2008).…”
Section: The Diversity Of Ficus Sppmentioning
confidence: 99%